Efektivitas Gadget Dalam Pembelajaran Persamaan dan Pertidaksamaan Linier Satu Variabel Menggunakan Google Chrome - Prasetyo, Bambang; Triani, Iftitah Evi; Fradisti, Meisya (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
Technology in this digital era has experienced a lot of progress, this development is marked by the emergence of an item commonly called a gadget. Gadgets are electronic devices that are commonly used for information media, learning media, and as entertainment. The purpose of this study is to analyze the effect of gadget use on learning which takes the material of linear equations and inequalities of one variable. The research method used is literature study and descriptive research with a qualitative approach carried out by students solving questions using a web-based platform. This research was conducted at SMK Kesehatan Bhakti Husada. Based on the results of the study with proper management, gadgets can also be an effective and relevant learning tool in the digital era, especially in teaching mathematical concepts interactively.